(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-103-112 The article deals with the reflection of the personality of Sergey Yesenin and the motives of his work in the poetry of Rasul Gamzatov. Back in the 1940s, Yesenin’s lyrics attracted the attention of the Avar poet, who worshipped his talent, translated into his native language the pinnacle work of “the most Russian poet” – the poem “Anna Snegina”. Even though both of the poets represent different epochs, peoples, and poetic schools, they have a lot in common. Both of them glorified the motherland, its history, people, their spiritual world, moral values, a woman, her beauty and love in their works. Key words: creativity, Sergey Esenin, Rasul Gamzatov, lyrics, reception, poet, theme